Meta-analysis of the effects of denosumab and romosozumab on bone mineral density and turnover markers in patients with osteoporosis - Hu, Mingwei; Zhang, Yifan; Guo, Jianjun; Guo, Cuicui; Yang, Xue; Ma, Xue; Xu, Hao; Xiang, Shuai (Frontiers in Endocrinology, 2023)
Abstract Purpose: To assess the alterations in bone mineral density and bone turnover marker concentrations following the administration of denosumab and romosozumab therapies in patients with osteoporosis. Methods: PubMed was searched for studies published until January 28, 2023, that investigated the clinical efficacy and bone turnover marker changes of denosumab and romosozumab in the treatment of osteoporosis, with a minimum follow-up of 3 months in each study. Studies were screened, and data on changes in bone mineral density (BMD), P1NP, and TRACP-5b levels after treatment were extracted and included in the analysis. Results: Six studies were analyzed. At 3 months after treatment, the romosozumab group showed greater changes in lumbar BMD and bone turnover markers. BMD of total hip and femoral neck was relatively delayed. Beginning at 6 to 12 months, romosozumab showed greater changes in bone mineral density and markers of bone turnover.. Conclusion: Both romosozumab and denosumab have antiosteoporotic effects, with greater effects on BMD and bone turnover markers observed within 12 months of romosozumab treatment. Key words: Osteoporosis; Denosumab; Romosozumab; Bone mineral density; Bone turnover marker Level evidence: Level III